Análise do transcriptoma da glândula venenífera de Rhinocerophis alternatus (Bothrops alternatus): identificação de metaloproteases e desintegrinas - Hirayama, Silvia Naomi Soida (Universidade Federal de São Carlos, 2011)
The desintegrinas are cys-rich polypeptides without enzymatic activity, some found in snake venoms with an adhesive motif to integrin, unleashing distinct responses. Several research groups have been studying snake venom disintegrins with focus in pharmacological applications in tumor progression and proliferation, angiogenesis, blood clotting, and osteoporosis. This work shows the results of the construction of cDNA library of Rhinocerophis alternatus venom gland, cloning and expression of ALT-C, a disintegrina-like protein, in bacterial system. The library was comprised of 812 sequences that were classified into: (i) coding for hypothetical protein or mismatched in databases (unknown) corresponding to 20.94%; (ii) transcripts for cellular process 17.86%; and (iii) transcripts coding for toxic protein with 61.21%. Among toxic proteins the SVMPs were the most abundant transcripts 58.59%. Other toxic transcripts were C-type lectins (15.56%), bradykinin potentiating peptides (11.8%), serineproteases (5.18%), cys-rich secretory proteins (2.28%), vascular endothelial growth factors (2.28%), L-amino acid oxidases (1.86%) and phospholipases A2 (1.45%). The percentages correspond to this snake venom effects, low enzymatic activity and hemorrhagic and clotting activity as main action, derived from the SVMPs, C-type lectin and serineproteases. One of the SVMPs contigs were chosen based on the similarity with ALT-C, the defined sequence was called ALT-Ch (ALT-C homologue) since there has 4 conservative substitutions compared to the previously determined sequence. The ALT-C-h sequence was used in PCR to inclusion the restriction site for BamHI and EcoRI, cloned in pGEX4T-1 and transformed into E. coli AD494 (DE3) for expression. The cell culture was grown until the log fase and induced with IPTG for 3 hours, the expressed protein's identity was confirmed by Western Blotting using Polyclonal antibody Anti-ALT-C. The construction of the R. alternatus venom gland cDNA library provides a source of interesting active biomolecules, such as desintegrinas, to pharmacological applications in pathologies involving integrins like angiogenesis, tumor progression and metastasis.
Keywords: DNA recombinante; Biblioteca de cDNA; Metaloprotease; Alternagina-C; Rhinocerophis alternatus; CIENCIAS BIOLOGICAS::GENETICA